Does gender matter for collaborative learning? - Ling Cen; Ruta, Dymitr; Powell, Leigh; Ng, Jason (2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2014)
In our recent work we have proven quantitatively that collaborative learning improves students' knowledge retention and boosts the quality of attained learning outcomes. In this research we investigate the role that the students' gender plays in their engagement during collaborative learning and their learning performance as assessed by the teacher. In the context of the EBTIC developed Collaborative Learning Environment deployed at Khalifa University along the sequence of three group courseworks over one semesters, we intend to explore the differences between the collaborative learning style and quality in female, male and mixed-gender groups. The series of detailed cross-gender learning engagement and performance comparisons indicate that female groups tend to work simultaneously and achieve better results while male group members engage less and work in sequence. As a result female groups exploit the added benefits of collaborative learning more than the male groups. What is striking, however, the members of the mixed-gender groups excel the most, significantly improving their engagement, focus and the quality of groupwork comparing to same-gender groups. We believe this outcome delivers yet another proof of the synergies and efficiencies of interactive learning in a diverse group of students and encourages mixing genders when composing groups for collaborative learning.